The effect of tooth bleaching on the shear bond strength of orthodontic brackets using self-etching primer systems - Akin, Mehmet; Aksakalli, Sertac; Basciftci, Faruk Ayhan; Demir, Abdullah (European Journal of Dentistry, 2013)
Objective: The purpose of this study was to determine the effect of 10% carbamide peroxide and 38% hydrogen peroxide bleaching agents on the shear bond strength of orthodontic brackets using self-etching primer systems.Methods: Forty five freshly extracted human premolar teeth were randomly divided into 3 groups of 15 teeth each: control (group 1), 10% carbamide peroxide at-home bleached (group 2), and 38% hydrogen peroxide in-office bleached (group 3). Three weeks later, all brackets were bonded using a self-etching primer system. The shear bond strength of these brackets was measured and recorded in MPa. Adhesive remnant index (ARI) scores were determined after the brackets failed. Data were analyzed using Kruskal- Wallis test, pairwise comparisons were made using the Mann-Whitney U test and ARI scores were analyzed using a chi-square test at a significance level of P<.05.Results: The shear bond strengths of group 1 (mean: 17.7 ± 9.7 MPa) were significantly higher (P<.05) than those of group 3 (mean: 9.9 ± 5.4 MPa). No significant differences were found between group 2 (mean: 12.3 ± 4.7) and either group 1 or group 3 (P>.05). ARI scores did not differ significantly among the 3 groups.Conclusions: The use of 10% carbamide peroxide bleaching does not significantly reduce shear bond strength values. In contrast, use of 38% hydrogen peroxide bleaching significantly reduces these values. (Eur J Dent 2013;7:55-60)
Keywords: Bleaching; self-etching primer; bond strength; orthodontic; bracket